2007
DOI: 10.2485/jhtb.16.61
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Formation of the Tooth Germ in a Rat Model of Fetal Alcohol Syndrome

Abstract: Abstract:The purpose of the present study was to elucidate the influence of alcohol ingestion in pregnant rats on the body and teeth of neonatal rats. Twenty two pregnant rats were divided into a normally-housed control group and alcohol-intake group exposed to alcohol during pregnancy, and 223 neonatal rats from these pregnant rats were used for the study. We observed the amount of water intake and the number of pups in mother rats, and body weight, eye-opening, and tooth development (postnatal day 1, 5, 15, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
1
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 24 publications
3
1
0
Order By: Relevance
“…In the present study, however, such histological alterations were not observed in the tooth germs in the 25%-ethanolexposed rats. These findings agree with those of other investigators 21) , who found that alcohol intake during pregnancy had no significant influence on cell morphogenesis or differentiation, despite a few days delay in tooth germ development in the ethanolintake rats. In evaluating the effect of ethanol on tooth development in an animal model, it is important to take into account the species and strain of animal used, as their ability to metabolize alcohol will affect ethanol concentration, administration route, duration of administration and period of exposure to be employed.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In the present study, however, such histological alterations were not observed in the tooth germs in the 25%-ethanolexposed rats. These findings agree with those of other investigators 21) , who found that alcohol intake during pregnancy had no significant influence on cell morphogenesis or differentiation, despite a few days delay in tooth germ development in the ethanolintake rats. In evaluating the effect of ethanol on tooth development in an animal model, it is important to take into account the species and strain of animal used, as their ability to metabolize alcohol will affect ethanol concentration, administration route, duration of administration and period of exposure to be employed.…”
Section: Discussionsupporting
confidence: 93%
“…Taken together with those of earlier studies 20,21) , the results of this study suggest that ingestion of ethanol during pregnancy alters fetal rat growth in a variety of ways, including litter size and body weight, although isocaloric pair-fed rats were not employed as controls. In addition, many reports have shown that ethanol suppresses development of other parts of the body, including the brain [22][23][24] , liver 25) , cranial bone and mandible 26,27) in an animal FAS model.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…These data corroborate the histological report observed in the 20-days-old group. They are also in agreement with the histological findings of Imai et al (2007) that in 20-days-old rats, tooth morphogenesis is almost complete and tooth eruption occurs.…”
Section: Discussionsupporting
confidence: 91%